Investigating the efficiency of mixtures based on supercritical CO2 and lubricants by friction tests under conditions similar to the machining of Ti6Al4V - Koulekpa, Koffi Samuel; Benked-Dar, Chadi; Elias-Birembaux, Hélène; Rossi, Frédéric; Poulachon, Gérard (Frontiers in Manufacturing Technology, 2024)
New supercritical carbon dioxide (scCO2)-based cutting fluids combining the cooling from scCO2 and lubrication from various additives are investigated in this study. Selected components, including ionic liquids, vegetable and mineral oils, water, and PEG, were introduced into supercritical CO2, and tribological tests were performed on a CNC lathe to analyze their influence on Ti6Al4V/WC-Co contact. Forces and temperatures were recorded to compare the perfomances of the scCO2-lubricant mixtures for future use in machining. The analysis of the apparent friction coefficient and sticking zone showed a noticeable decrease by ionic liquids when combined with scCO2 at a speed of 100 m/min and 4 mL/min delivery flow rate. The other lubricants (water and PEG vegetable oils) performed similarly to standard mineral oil and are less expensive, which could help in developing future low-cost yet effective cooling and lubrication methods for the machining industry.